Related Markers for the Precision Diagnosis of Complex Appendicitis in Children - Zhou, Jialin; Xu, Wenjing; Wang, Jitao; Fan, Zhe (Frontiers in Pharmacology, 2022)
Acute appendicitis is the most common surgical emergency in children. Despite the high incidence rate of appendicitis, it is sometimes misdiagnosed or missed. Complex appendicitis (CA) in children is characterized by a critical condition, several complications, and high mortality. Precision distinguishing between simple appendicitis and CA correctly is key to choosing appropriate treatment. A safe, cheap, rapid, extensive and accurate diagnostic marker of appendicitis will be of great significance for emergency general surgeons to treat suspected CA. Many studies have investigated possible diagnostic markers for the diagnosis of CA in children. In this study, studies related to CA in children in recent years are summarized, and the related markers and scoring system for the diagnosis of CA in children are summarized.